ABILITY TO READ STUDENTS' UNDERSTANDING USING LEARNING “COOPERATIVE INTERGRATED READING” - Sri Mulyani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: The purpose of this study namely, to determine the ability to read students'understanding using Cooperative Integrated Reading learning, while the method used in this studyis descriptive qualitative. The techniques for collecting data are collecting answer sheets whichinclude: 1) finding the main idea (main idea or theme) in the discourse / text, 2) restating thecontents of the discourse/text that has been read, and 3) developing the main idea / main idea orpictures. After conducting the research, the following results were obtained. The reading ability ofstudents, before using Cooperative Integrated Reading learning in the R2A class, was 2403 or 68%(bad), and after using Cooperative Integrated Reading learning, the students' abilities changed,namely 2.403 or 80% 9good), and the ability to read comprehension of students in class R2Bbefore using Cooperative Integrated Reading learning, namely 2.162 or 72% (low). After usingCooperative Integrated Reading, there was a change, namely 2,425 or 81% (baik). So, it is clearthat the ability to read students' understanding using Cooperative Integrated Reading learning isable to provide progress properly and precisely.Key Words: Reading Comprehension, Cooperative Integrated Reading, learning